Bridging the Gap between Theory and Practice; the Active Role of Inpatient Pharmacists in Therapeutic Drug Monitoring - Abrar F Alhameed; Sara Al Khansa; Hani Hasan; Sherine Ismail; Mohammed Aseeri (MDPI AG, 2019)
Many hospitals face barriers in the implementation of TDM services, this study aimed to evaluate a pharmacist-led TDM service to optimize patients’ outcomes. Adult patients who were administered vancomycin, gentamicin, or amikacin were included. The pre-phase included a retrospective assessment of patients and the intervention phase consisted of an educational program. The post-phase assessed patients based on TDM services provided by inpatient pharmacists on a 24-h, 7-day basis for 3 months. The primary outcome was to assess the mean difference in proportion of correct initial doses of prescribing orders. Secondary outcomes included assessing the mean differences in proportions of correct dose adjustments and correct drug sampling time. Seventy-five patients in each phase were eligible. Patients who received optimal initial dosing in the post-phase showed a higher statistical significance, mean difference of 0.31, [95% CI (0.181⁻0.4438), p < 0.0001]. Patients in the post-phase received more optimal dose adjustments, mean difference of 0.1, [95% CI (−0.560⁻0.260), p = 0.2113]. Drug levels were ordered more correctly in the post-phase, mean difference of 0.03, [95% CI (−0.129⁻0.189), p = 0.7110]. This study demonstrated the important role of TDM services led by pharmacists in optimizing the initial dosing for these antibiotics.